Spontaneous Heterotopic Pregnancy: A Case Report and Review of Diagnostic Dilemma and Challenges of Surgical Management in a Resource-Limited Environment (Western Journal of Medical and Biomedical Sciences, 2023)
Heterotopic pregnancy is the simultaneous occurrence of normal intrauterine and extrauterine gestations. It is a very uncommon complication of gestation and more common in artificial conceptions like assisted reproduction techniques than in natural conceptions. On the whole, it is a life-threatening pathology. The diagnosis is often missed during radiological investigations due to its rarity. A painstaking sonographic evaluation is needed to rule out the presence of heterotopic gestation and thus help in prompt diagnosis and appropriate management. Early diagnosis of this pathology decreases the likelihood of complications. We hereby report a case of heterotopic pregnancy presenting with amenorrhea of seven and half weeks and acute excruciating lower abdominal pain with associated episodes of spotting of bright red blood per vagina of four days duration. The diagnosis of a normal pregnancy co-existing with a ruptured extrauterine gestation was made on a thorough ultrasound examination. The patient was managed with exploratory laparotomy and left salpingectomy. The intrauterine pregnancy course was uneventful with a delivery of a live baby at term. This case report emphasizes the need to carefully examine the adnexa even with the visualization of normal pregnancy on ultrasound interrogation to rule out heterotopic pregnancy
Keywords: Heterotopic pregnancy; Extrauterine pregnancy; Amenorrhoea; Exploratory laparotomy